Twin gestation in a uterus didelphys with only one functional cervix: A case report - Rebecca J. Post; Claire L. Templeman; Richard M. Benoit (Elsevier, 2019)
Introduction: Twin gestation in a uterus didelphys with one fetus in each uterine cavity is rare and presents unique challenges in antepartum and intrapartum care. Case Presentation: A 35-year-old woman with a uterus didelphys became pregnant with twins, with one fetus in each uterus, after intrauterine insemination of a single visible cervix. Multiplanar ultrasonography showed the presence of one complete cervix and a second hypoplastic cervix; it was unclear whether she could deliver both twins vaginally. Her pregnancy was complicated by fetal growth restriction of twin B. At 38 weeks, the patient underwent scheduled cesarean section and delivered two viable twins. Conclusion: Determining the precise anatomy of Mullerian duct anomalies, including the cervix and vagina, is important for obstetrical management. Keywords: Twin gestation, Uterus didelphys, Hypoplastic cervix, Mullerian duct anomalies, Cervical anomalies